The Main Ideas of Libertarianism - Jasiński, Karol (Studia Warmińskie, 2022)
The purpose of this paper is to present the core ideas of libertarianism. Its main representatives include Jay A. Nock, Ayn Rand, Robert Nozick, Murray N. Rothbard and Hans H. Hoppe. Libertarianism, with its many doctrines, currents and movements, means a cultural current, a philosophical theory or an ideology. It seems that libertarianism should be regarded primarily as a variant of liberalism, especially classical liberalism as a certain doctrine of socio-political life (which, however, has certain metaphysical-anthropological presumptions), and an attempt to develop it consistently. Despite the different varieties of libertarianism, some are radical and others moderate, it can be characterised by a few core ideas, which include the idea of the free individual, private property and the free market, justice, human rights, criticism of the state and support for civil society.